Status, Threats and Conservation of the Wetland Ecosystem Dominated with Mangroves in India - Dhadse, Sharda; Majumdar, Pramila; Valluri, Ashwini; Sakhare, Purushottam (Plantae Scientia, 2021)
Mangroves are one of the most undermined biological systems. They have immense ecological and economic advantages. Consistent, increment in natural and coastal development like a change of wetlands for hydroponics, construction for tourism, the tsunami has led to the demolishment of mangrove environments in India. The inhabitants of minor zones are at risk of losing their livelihood and there is a threat to the existence of the mangrove ecosystem. It has been noted that from a decade ago, about 40% of the Indian mangrove territories have been lost. At present, the environmental changes and increased anthropogenic activities have become a significant concern for the conservation and sustaining of the mangroves. Conservation of mangrove environment can be accomplished by increasing awareness about their significance among various stakeholders and safeguarding them through mandatory national policy and regulations. A specific policy like Coastal Zone Regulation has been formulated to ensure mangrove conservation, sustainable existence of local community habitat along the coastal area, fishing community, and coastal stretches for marine habitat have been protected.